Bahasa Indonesia sebagai Alat Pencegahan Korupsi: Studi Linguistik terhadap Kampanye Anti-Korupsi Internal dan Eksternal di Kejaksaan Negeri Kabupaten Gorontalo - Dali, Meilina Widya; Piu, Chindy Rosvhita; Madaun, Marsella Aurelya; Nur, Annisa Desrilla; Domili, Madhava Ainnurrahman; Utiarahman, Alzena Syaikah Putri; Abas, Siti Fahilah; Ramadhan, Fakhri Auliah; Dungga, Rahmat Jupri; Rahman, Moh. Danial; Ihsan, Muh. Rizky Apriawan; Dawali, Farel Setiawan; Harmain, Muchamad Raihzan (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Indonesian is the official national language that plays a strategic role as a means of communication, education, and prevention in efforts to eradicate corruption. This study aims to analyze the use of the Indonesian language as an instrument for corruption prevention through internal and external anti-corruption campaigns conducted by the Prosecutor’s Office. The research method employed is descriptive with a qualitative approach. Data collection techniques include observation, interviews, and documentation of legal counseling activities and anti-corruption campaign materials. The results show that the Indonesian language is used in a straightforward, simple, and communicative manner so that anti-corruption messages can be understood by all levels of society. In internal campaigns, the use of legal terminology is adjusted to the professional context of employees to ensure clarity and avoid ambiguity. Meanwhile, in external campaigns, the language used is persuasive through direct socialization to the community and the use of simple slogans. Thus, the Indonesian language functions not only as a communication tool, but also as an educational medium and a strategic instrument in building legal awareness and preventing acts of corruption.